LEGAL RESPONSIBILITY OF DOCTORS WHO WITH HOLD THERAPY IN PATIENTS WHO DO NOT PAY FOR MEDICAL TREATMENT IN THE HOSPITAL - Dewi Puspitorini Husodo; Sutarno; Asmuni (JILPR Journal Indonesia Law and Policy Review, 2023)
Every year in Indonesia, hundreds of patients run away due to medical financing. No payment for medical services, consumables, and infrastructure costs used for the treatment of these patients causes material and immaterial losses for health workers and hospitals. As a result of this rampant, several hospitals, especially private hospitals, have implemented a down payment system. The problem and purpose of this study is to analyze the legality and legal responsibility of doctors who stop therapy for patients who do not pay for medical treatment. This study uses normative research methods with statutory approaches, conceptual approaches and comparative approaches. Doctors in carrying out their medical practice have the right to receive compensation for services and patients have the obligation to pay fees for the services they receive in accordance with the Medical Practice Law. If the patient does not fulfill his obligations to pay for the services he has received, the hospital and the doctor can sue the patient for default. If the patient does not fulfill his obligations to pay for the services he has received, the hospital and the doctor can sue the patient for default. If in the process of discontinuing therapy causes the patient to fall into a state of serious injury, disability or death, doctors and hospitals may be subject to criminal responsibility, civil and administrative liability. If the patient does not fulfill his obligations to pay for the services he has received, the hospital and the doctor can sue the patient for default. If in the process of discontinuing therapy causes the patient to fall into a state of serious injury, disability or death, doctors and hospitals may be subject to criminal responsibility, civil and administrative liability.